Neutrophil-Lymphocyte Ratio (NLR) as A Predictor for Non-ST Elevation Myocardial Infarction (NSTEMI) in the Emergency Room - Zunardi, Lutfi Hafiz; Anjarwani, Setyasih; Prasetya, Indra; Satrijo, Budi; Rahimah, Anna Fuji (Heart Science Journal, 2024)
AbstractBackground: The usefulness of the NLR as an approach to identifying cases of acute coronary syndrome (ACS) needs to be improved.Objective: This research was designed to determine the effectiveness of the NLR in identifying individuals who presented to the emergency room complaining of anginal due to ACS.Methods: The single-center cross-sectional study was performed at Saiful Anwar General Hospital in Malang, East Java, Indonesia, from July 2020 to December 2023. Patients were involved in this study with complaints of angina suspected of ACS. During further observation in the emergency room, based on the findings of the troponin I analysis, individuals were divided into unstable angina pectoris (UAP) and NSTEMI.Results: Study results were collected from 282 individuals diagnosed with Non-ST Elevation Acute Coronary Syndrome (NSTEACS), with 75.9% male and a mean age of 58.39 ± 10.27 years. The NLR threshold was 4.5 (AUC: 0.78, 95% CI: 0.765–0.867, P <.001) assessed during admission, which showed a sensitivity of 79% and a specificity of 78% in accurately predicting the probability of subsequent troponin positivity. Multivariate analysis revealed that the NLR at hospitalization remained an essential marker of troponin positivity during follow-up.Conclusions: In the end, NLR could be considered an initial test in emergency services to predict the diagnosis of NSTEMI in people experiencing angina.